Positive psychological capital. Validation of the Spanish version of the PCQ questionnaire. - Azanza, Garazi; Domínguez, África J.; Moriano, Juan A.; Molero, Fernando J. (Anales de Psicología / Annals of Psychology, 2013)
This study describes the construct of positive psychological capital (Luthans and Youssef, 2004) and the validation of the Spanish version of the PCQ (Psychological Capital Questionnaire) in a sample of 372 employees. This questionnaire measures four components, although related, of the broader concept of psychological capital. These components are self-efficacy, hope, optimism and resilience. Structural equation modeling revealed that the Spanish version of the questionnaire shows a high reliability and convergent and discriminant validity. Results, and contributions, and limitations of the present study are discussed.